2015
DOI: 10.1083/jcb.201409063
|View full text |Cite
|
Sign up to set email alerts
|

The cell biology of fat expansion

Abstract: Adipose tissue is a complex, multicellular organ that profoundly influences the function of nearly all other organ systems through its diverse metabolite and adipokine secretome. Adipocytes are the primary cell type of adipose tissue and play a key role in maintaining energy homeostasis. The efficiency with which adipose tissue responds to whole-body energetic demands reflects the ability of adipocytes to adapt to an altered nutrient environment, and has profound systemic implications. Deciphering adipocyte ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
417
0
14

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 462 publications
(437 citation statements)
references
References 164 publications
(216 reference statements)
6
417
0
14
Order By: Relevance
“…Therefore, despite the insulin resistance, fat expansion in the obese provides a sink for glucose, which would otherwise accumulate in the bloodstream and further impair glucose tolerance. The converse problem, namely, the inability of adipose tissue to expand, is also conducive to reduced glucose tolerance and dyslipidemia (21).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, despite the insulin resistance, fat expansion in the obese provides a sink for glucose, which would otherwise accumulate in the bloodstream and further impair glucose tolerance. The converse problem, namely, the inability of adipose tissue to expand, is also conducive to reduced glucose tolerance and dyslipidemia (21).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, visceral obesity and the consequent adipose metabolic dysfunction represent important risk factors for the development and progression of NAFLD [43,44]. Obesity may lead to an imbalanced production of pro-and antiinflammatory adipokines secreted from adipose tissue, which contributes to the pathogenesis of NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Silencing FoxO1 can potently reduce autophagy activity and FSP27 level, suppressing adipocyte differentiation and LD growth. Given that LD expansion contributes to adipocyte hypertrophy and adipose expansion, 6,29,45 further study targeting the FoxO1-autophagy axis may result in therapeutic options to treat obesity.…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40][41][42] We and others found that FoxO1 also regulated adipogenesis, 3,43,44 a process which may promote adipose expansion via hyperplasia. 6,29,45 Moreover, aberrant adiposity may result from adipocyte or LD hypertrophy. 29,45 In this study, we showed for the first time that FoxO1 regulated LD size and number via an autophagy-FSP27 axis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation